Copper-based catalyst for starch hydrogenation sugar conversion as well as preparation method and application of copper-based catalyst
By preparing a copper-based catalyst, the aging treatment of copper saline solution and alkali and the mixing of support, the problem of easy deactivation of active sites of copper-based catalysts and low selectivity is solved, and an efficient, stable and environmentally friendly starch hydrogenation conversion process is achieved.
Patent Information
- Application Number
- CN202411787094.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
AI Technical Summary
The existing copper-based catalysts have problems such as inactivating active sites and low selectivity during the hydrogenation of starch into glucose, which limits their catalytic efficiency.
Copper-based catalyst was prepared by adding alkali to the copper saline solution and aging, filtration, uniformly mixing the hydroxide precipitation and support, tablet forming, and calculating at 250-900°C and reducing it with hydrogen.
The catalyst has good stability, is not easy to be inactivated, has a long life, is simple in production and is cheap in price, can efficiently catalyze starch sugar production, has a low process cost, and is environmentally friendly, simple and easy to control.
Smart Images

Figure CN119524848A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic hydrogenation, and specifically relates to a copper-based catalyst for hydrogenating starch into sugar, and a preparation method and application thereof. Background Art
[0002] Starch is an extremely abundant and renewable carbohydrate resource in nature, widely found in many plants such as grains, potatoes, and beans. Decomposing starch into glucose through chemical or biological methods can not only provide important raw materials for the food, medicine, chemical and other industries, but is also one of the key steps in producing renewable energy such as bioethanol and biodiesel.
[0003] Traditional starch sugar production technology mainly relies on acid hydrolysis or enzyme hydrolysis technology. Although the acid hydrolysis method is mature, it has problems such as environmental pollution, equipment corrosion and high cost of subsequent neutralization treatment; while the enzyme hydrolysis method has mild conditions and strong specificity, but the enzyme is expensive, has poor stability and is easily affected by operating conditions, which limits its large-scale application. Therefore, exploring more efficient and environmentally friendly starch conversion technology has become a research focus.
[0004] In recent years, the use of metal catalysts to promote the direct hydrogenation or hydrolysis of amorphous polysaccharides such as starch has become a new research trend. In particular, transition metal oxides have shown great potential in the field of catalysis due to their unique electronic structure and catalytic activity. Among them, copper-based catalysts are cheap, readily available, and environmentally friendly, and have been proven to effectively promote the degradation of cellulose to produce glucose. However, when copper-based catalysts are used alone, they often have problems such as easy deactivation of active sites and low selectivity, which limits their catalytic efficiency. In order to improve their catalytic performance, researchers have begun to explore loading active metal copper on different carriers to form composite catalysts, in order to optimize the catalytic process by improving the dispersibility of the catalyst, increasing the accessibility of active sites, and adjusting the surface acid-base properties.
[0005] The application of copper-based supported catalysts in the hydrogenation of starch to glucose is still in the initial exploration stage, and its catalytic mechanism, optimal preparation conditions, reaction path optimization, and catalyst regeneration and recycling are still under further study. Therefore, the development of an efficient, stable, and recyclable copper-based catalyst for the direct hydrogenation of starch can not only fill the technical gap in this field, but also provide new ways and technical support for the in-depth development and efficient utilization of starch resources, which has important theoretical significance and practical application value. Summary of the invention
[0006] In view of the above-mentioned prior art problems, the present invention provides a copper-based catalyst for starch hydrogenation and sugar conversion, and a preparation method and application thereof. The catalyst can efficiently catalyze starch sugar production, has good stability, is not easy to deactivate, has a long service life, is simple to prepare, is low in price, and is easy to control.
[0007] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a copper-based catalyst for starch hydrogenation and sugar conversion comprises the following steps: (1) adding alkali to a copper salt aqueous solution, aging and filtering to obtain a hydroxide precipitate; (2) uniformly mixing the hydroxide precipitate and the carrier to obtain a catalyst precursor, and pressing the catalyst precursor into tablets; (3) The formed catalyst precursor obtained in step (2) is calcined at 250-900° C., and then reduced with hydrogen to obtain the copper-based catalyst.
[0008] Preferably, the copper salt in step (1) is one or more of copper nitrate, copper acetate or copper sulfate.
[0009] Preferably, the base in step (1) is aqueous ammonia.
[0010] Preferably, in step (1), the pH is controlled to be 10.
[0011] Preferably, the aging time in step (1) is 0.1 to 48 hours.
[0012] Preferably, the carrier in step (2) is one or more of silicon oxide, aluminum oxide, zirconium oxide, titanium oxide, activated carbon, kaolin or diatomaceous earth.
[0013] Preferably, step (2) further comprises the step of drying the catalyst precursor. More preferably, the drying temperature is 60-120°C.
[0014] Preferably, the reduction temperature in step (3) is 150-300°C.
[0015] Preferably, the reduction time in step (3) is 0.25 to 24 hours.
[0016] The invention also provides a copper-based catalyst prepared by the preparation method.
[0017] The present invention also provides application of the copper-based catalyst prepared by the preparation method.
[0018] The application includes: hydrogenating starch into sugar in a batch reactor under hydrogen conditions.
[0019] Preferably, the hydrogenation temperature is 100~250°C, the hydrogen pressure is 0.1~8.0 MPa, the starch is in the form of a solution, the concentration of the starch solution is 1wt%~50wt%, the flow rate of the starch solution is 0.1~3mL / min, the filling height of the catalyst in the intermittent reactor is 5~120 cm, and the tail gas flow rate is 5~10 mL / min.
[0020] The beneficial effects of the present invention are: When the catalyst of the present invention is used to convert starch, the raw material can be agricultural waste, which has a wide range of sources.
[0021] The catalyst of the present invention not only has good stability, is not easy to deactivate, can realize continuous production, and has a long service life, but also has a simple and easy preparation method and a low price, so that the cost of the entire process is low.
[0022] The catalyst of the present invention is used to convert starch. During the process, no waste gas or waste water is generated, no neutralization process is required, and no salt is generated. The process is relatively simple and easy to control. It is a green and sustainable new process route.
[0023] The catalyst of the invention can fully utilize the effective components of starch, and the obtained product has a high sugar concentration, which provides raw materials for the subsequent preparation of high value-added chemicals and is conducive to industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the TEM image of the precursor in Example 1.
[0025] Figure 2 is a TEM image of the catalyst obtained after reduction in Example 1. DETAILED DESCRIPTION
[0026] The present invention will be described in more detail below by way of examples, which however do not limit the scope of protection of the present invention. Example 1
[0027] Catalyst preparation: Take a certain amount of copper acetate and prepare a 2 mol / L aqueous solution in a three-necked flask. Add 20% ammonia water to generate Cu(OH)2 precipitate, heat to 60°C, and age for 4 hours. Add SiO2 carrier powder (1:5 mass ratio, the same below), filter, wash, and dry at 80°C. The precursor is calcined at 250°C, and then reduced in a hydrogen atmosphere at 250°C for 4 hours to obtain a Cu / SiO2 catalyst.
[0028] Catalyst performance evaluation: In a fixed bed reactor, the reaction temperature was set to 180 °C, the hydrogen pressure was 2.5 MPa, the starch solution concentration was 20 wt%, the flow rate was 0.8 mL / min, the catalyst filling height was 60 cm, and the glucose yield was 81.2%. Example 2
[0029] Catalyst preparation: Use a mixed solution of copper sulfate and copper nitrate (1:1 ratio) in a three-necked flask to prepare a concentration of 4 mol / L. Slowly add 30% ammonia water until a precipitate is formed, maintain the solution at 45°C, and age for 0.5 hours. Add Al2O3 carrier (1:3 ratio), filter, wash, and dry at 120°C, then calcine the precursor at 400°C, and perform hydrogen reduction at 170°C for 6 hours.
[0030] Catalyst performance evaluation: The reaction conditions were temperature 220°C, hydrogen pressure 3.0 MPa, starch concentration 30%, flow rate 2.0 mL / min, catalyst filling height 80 cm, and glucose yield 89.5%. Example 3
[0031] Catalyst preparation: Prepare 3 mol / L copper nitrate aqueous solution, add 28% ammonia water to form a precipitate, heat the solution to 70°C, and age for 12 hours. Add ZrO2 carrier (1:10 ratio), filter, wash, dry at 90°C, and calcine the precursor at 600°C. Hydrogen reduction is performed at 300°C for 12 hours.
[0032] Catalyst performance evaluation: The reaction conditions were 140°C, hydrogen pressure 0.5 MPa, starch concentration 10%, flow rate 0.3 mL / min, catalyst filling height 20 cm, and glucose yield of 82.9%. Example 4
[0033] Catalyst preparation: Use copper sulfate solution (2 mol / L), add 35% ammonia water, age for 36 hours. Add TiO2 carrier (1:2 ratio), filter, wash and dry at 110℃. The precursor is calcined at 700℃ and hydrogen reduction is carried out at 280℃ for 1h.
[0034] Catalyst performance evaluation: The reaction conditions were 200°C, hydrogen pressure 6.0 MPa, starch concentration 40%, flow rate 2.5 mL / min, catalyst filling height 100 cm, and glucose yield of 88.3%. Example 5
[0035] Catalyst preparation: Prepare 1.5 mol / L copper acetate solution, use 22% ammonia water, and age for 1 hour. Mix with activated carbon carrier (1:4 ratio), filter, wash, and dry at 70°C. The precursor is calcined at 500°C, and hydrogen reduction is performed at 190°C for 20 h.
[0036] Catalyst performance evaluation: The reaction conditions were 170°C, hydrogen pressure 1.0 MPa, starch concentration 25%, flow rate 1.0 mL / min, catalyst filling height 50 cm, and glucose yield of 92.4%. Example 6
[0037] Catalyst preparation: Use a mixed solution of copper nitrate and copper sulfate (2:1 ratio) to prepare a concentration of 5 mol / L, add 27% ammonia water, and age for 8 hours. Add kaolin carrier (1:6 ratio), filter, wash, and dry at 100°C. The precursor is calcined at 800°C, and hydrogen reduction is performed at 220°C for 4 hours.
[0038] Catalyst performance evaluation: The reaction conditions were 240°C, hydrogen pressure 7.0 MPa, starch concentration 5%, flow rate 0.5 mL / min, catalyst filling height 120 cm, and glucose yield of 57.9%. Example 7
[0039] Catalyst preparation: Prepare 3 mol / L copper nitrate solution, add 25% ammonia water, and age for 48 hours. Add alumina carrier (1:8 ratio), filter, wash, and dry at 60°C. The precursor is calcined at 350°C, and hydrogen reduction is performed at 150°C for 24 hours.
[0040] Catalyst performance evaluation: The reaction conditions were 140°C, hydrogen pressure 2.0 MPa, starch concentration 15%, flow rate 1.0 mL / min, catalyst filling height 50 cm, and glucose yield of 98.9%. Example 8
[0041] Catalyst preparation: 2.5 mol / L copper acetate solution was added with 26% ammonia water and aged for 6 hours. Al2O3 and SiO2 carriers were mixed (1:1 ratio, total ratio was 1:7), filtered, washed, and dried at 80°C. The precursor was calcined at 450°C and hydrogen reduction was performed at 210°C for 16 h.
[0042] Catalyst performance evaluation: The reaction conditions were 190°C, hydrogen pressure 4.0 MPa, starch concentration 1%, flow rate 0.2 mL / min, catalyst filling height 90 cm, and glucose yield of 69.8%. Example 9
[0043] Catalyst preparation: Prepare 1 mol / L copper sulfate solution, use 24% ammonia water, and age for 0.1 hour. Add ZrO2 and TiO2 mixed carrier (1:1 ratio, total ratio is 1:9), filter, wash, and dry at 90℃. The precursor is calcined at 750℃, and hydrogen reduction is carried out at 270℃ for 0.5 h.
[0044] Catalyst performance evaluation: The reaction conditions were 230°C, hydrogen pressure 5.5 MPa, starch concentration 45%, flow rate 2.8 mL / min, catalyst filling height 70 cm, and glucose yield of 86.7%. Example 10
[0045] Catalyst preparation: Use copper nitrate solution (3 mol / L), add 29% ammonia water, and age for 24 hours. Add activated carbon and kaolin mixed carrier (1:1 ratio, total ratio is 1:3), filter, wash, and dry at 110°C. The precursor is calcined at 650°C, and hydrogen reduction is carried out at 240°C for 3 h.
[0046] Catalyst performance evaluation: The reaction conditions were 150°C, hydrogen pressure 2.2 MPa, starch concentration 10%, flow rate 0.4 mL / min, catalyst filling height 40 cm, and glucose yield of 93.1%. Embodiment 11
[0047] Catalyst preparation: Prepare 2 mol / L copper acetate solution, add 30% ammonia water, and age for 18 hours. Add SiO2 and diatomaceous earth mixed carrier (1:1 ratio, total ratio is 1:4), filter, wash, and dry at 75°C. The precursor is calcined at 550°C, and hydrogen reduction is carried out at 180°C for 10 hours.
[0048] Catalyst performance evaluation: The reaction conditions were 210°C, hydrogen pressure 3.5 MPa, starch concentration 20%, flow rate 1.8 mL / min, catalyst filling height 55 cm, and glucose yield of 87.3%. Example 12
[0049] Catalyst preparation: A mixed solution of copper sulfate and copper nitrate (1:2 ratio) was prepared to a concentration of 4.5 mol / L, 25% ammonia water was added, and the mixture was aged for 16 hours. A mixed carrier of Al2O3 and ZrO2 (1:1 ratio, total ratio of 1:6) was added, filtered, washed, and dried at 105°C. The precursor was calcined at 900°C, and hydrogen reduction was performed at 260°C for 2 h.
[0050] Catalyst performance evaluation: The reaction conditions were 130°C, hydrogen pressure 0.6 MPa, starch concentration 30%, flow rate 0.6 mL / min, catalyst filling height 25 cm, and glucose yield 82.0%. Example 13
[0051] Catalyst preparation: Prepare 1.8 mol / L copper nitrate solution, add 31% ammonia water, and age for 10 hours. Mix TiO2 and activated carbon carrier (1:1 ratio, total ratio is 1:5), filter, wash, and dry at 85°C. The precursor is calcined at 480°C, and hydrogen reduction is carried out at 230°C for 6 hours.
[0052] Catalyst performance evaluation: The reaction conditions were 250°C, hydrogen pressure 8.0 MPa, starch concentration 50%, flow rate 3.0 mL / min, catalyst filling height 110 cm, and glucose yield 85.5%. Embodiment 14
[0053] Catalyst preparation: Use copper acetate solution (2.2 mol / L), add 28% ammonia water, and age for 3 hours. Add kaolin and diatomaceous earth mixed carrier (1:1 ratio, total ratio is 1:2), filter, wash, and dry at 65°C. The precursor is calcined at 380°C, and hydrogen reduction is carried out at 150°C for 14 h.
[0054] Catalyst performance evaluation: The reaction conditions were 110°C, hydrogen pressure 0.2 MPa, starch concentration 15%, flow rate 0.1 mL / min, catalyst filling height 15 cm, and glucose yield of 84.2%. Embodiment 15
[0055] Catalyst preparation: Prepare 5 mol / L copper sulfate solution, use 33% ammonia water, and age for 7 hours. Add ZrO2, TiO2 and SiO2 mixed carrier (ratio is 1:1:1, total ratio is 1:7), filter, wash and dry at 95℃. The precursor is calcined at 720℃, and hydrogen reduction is carried out at 290℃ for 0.75 h.
[0056] Catalyst performance evaluation: The reaction conditions were 165°C, hydrogen pressure 1.5 MPa, starch concentration 22%, flow rate 0.7 mL / min, catalyst filling height 85 cm, and glucose yield 81.8%. Example 16
[0057] Catalyst preparation: A mixed solution of copper nitrate and copper acetate (3:2 ratio) was prepared to a concentration of 3.5 mol / L, 26% ammonia water was added, and the mixture was aged for 20 hours. Al2O3 and activated carbon mixed carrier (ratio 2:1, total ratio 1:4) were added, filtered, washed, and dried at 100°C. The precursor was calcined at 580°C, and hydrogen reduction was performed at 200°C for 18 h.
[0058] Catalyst performance evaluation: The reaction conditions were 205°C, hydrogen pressure 4.5 MPa, starch concentration 50%, flow rate 0.9 mL / min, catalyst filling height 65 cm, and glucose yield 78.6%. Embodiment 17
[0059] Catalyst preparation: Prepare 2.7 mol / L copper sulfate solution, add 34% ammonia water, and age for 30 hours. Mix SiO2 and activated carbon carrier (ratio 3:1, total ratio 1:6), filter, wash, and dry at 78°C. The precursor is calcined at 620°C, and hydrogen reduction is performed at 175°C for 5 h.
[0060] Catalyst performance evaluation: The reaction conditions were 145°C, hydrogen pressure 0.4 MPa, starch concentration 20%, flow rate 1.4 mL / min, catalyst filling height 35 cm, and glucose yield 90.9%. Embodiment 18
[0061] Catalyst preparation: Use copper acetate solution (1.7 mol / L), add 29% ammonia water, and age for 14 hours. Add kaolin, diatomaceous earth and ZrO2 mixed carrier (ratio is 1:1:1, total ratio is 1:8), filter, wash and dry at 82℃. The precursor is calcined at 460℃, and hydrogen reduction is carried out at 250℃ for 1 h.
[0062] Catalyst performance evaluation: The reaction conditions were 225°C, hydrogen pressure 6.5 MPa, starch concentration 8%, flow rate 0.55 mL / min, catalyst filling height 95 cm, and glucose yield of 67.3%. Embodiment 19
[0063] Catalyst preparation: Prepare 4.2 mol / L copper nitrate solution, add 32% ammonia water, and age for 5 hours. Mix TiO2, Al2O3 and activated carbon carrier (ratio 1:1:1, total ratio 1:5), filter, wash, and dry at 92°C. The precursor is calcined at 780°C, and hydrogen reduction is performed at 300°C for 0.25 h.
[0064] Catalyst performance evaluation: The reaction conditions were 100°C, hydrogen pressure 0.1 MPa, starch concentration 12%, flow rate 0.25 mL / min, catalyst filling height 15 cm, and glucose yield 55.1%. Embodiment 20
[0065] Catalyst preparation: Use copper sulfate solution (2.4 mol / L), add 27% ammonia water, and age for 22 hours. Add SiO2, ZrO2 and activated carbon mixed carrier (ratio of 1:2:1, total ratio of 1:3), filter, wash, and dry at 72°C. The precursor is calcined at 520°C, and hydrogen reduction is carried out at 195°C for 9 hours.
[0066] Catalyst performance evaluation: The reaction conditions were 185°C, hydrogen pressure 2.8 MPa, starch concentration 28%, flow rate 1.1 mL / min, catalyst filling height 75 cm, and glucose yield of 82.2%.
Claims
1. A method for preparing a copper-based catalyst for starch hydrogenation and sugar conversion, characterized in that: The steps include: (1) adding alkali to a copper salt aqueous solution, aging and filtering to obtain a hydroxide precipitate; (2) uniformly mixing the hydroxide precipitate and the carrier to obtain a catalyst precursor, and pressing the catalyst precursor into tablets; (3) The formed catalyst precursor obtained in step (2) is calcined at 250-900° C., and then reduced with hydrogen to obtain the copper-based catalyst.
2. The preparation method according to claim 1, characterized in that: The copper salt described in step (1) is one or more of copper nitrate, copper acetate or copper sulfate.
3. The preparation method according to claim 1, characterized in that: The base described in step (1) is aqueous ammonia.
4. The preparation method according to claim 1, characterized in that: The aging time in step (1) is 0.1 to 48 hours.
5. The preparation method according to claim 1, characterized in that: The carrier in step (2) is one or more of silicon oxide, aluminum oxide, zirconium oxide, titanium oxide, activated carbon, kaolin or diatomaceous earth.
6. The preparation method according to claim 1, characterized in that: Step (2) further comprises the step of drying the catalyst precursor; preferably, the drying temperature is 60-120°C.
7. The preparation method according to claim 1, characterized in that: The reduction temperature in step (3) is 150-300°C.
8. A copper-based catalyst obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the copper-based catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: include: Starch is hydrogenated and converted into sugars in a batch reactor under hydrogen conditions.
10. The use according to claim 9, characterized in that The hydrogenation temperature is 100-250° C., the hydrogen pressure is 0.1-8.0 MPa, the starch is in the form of a solution, the concentration of the starch solution is 1wt%-50wt%, the flow rate of the starch solution is 0.1-3mL / min, the filling height of the catalyst in the intermittent reactor is 5-120 cm, and the tail gas flow rate is 5-10 mL / min.